Concepts of self-control and zuhud in character education: A perspective of stoicism and sufism - Muhammad Ilham; M. Abdullah Darraz; Ai Fatimah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
This research aims to comparatively examine the correlation between stoicism and the teachings of zuhud in Sufism related to self-control and zuhud attitude towards character education. These two concepts are assumed to have a positive relationship so that they can be used complementarily. This research was conducted through a qualitative method based on literature study. The author uses cognitive psychology and philosophical approach models regarding actual problems, and uses the content analysis method. The results of this study show that the Stoicism concept of self-control is very relevant to be used by Muslims in this century, especially when associated with the teachings of zuhud in education and human character building. This study concludes that the stoicism of Stoicism and zuhud in Sufism meet at the same point, namely the need for self-control and emotions in humans to educate character in order to accept and face every problem of life that confronts them.